Assessment of Air Pollution by PM10 and PM2.5 in Nawabshah City, Sindh, Pakistan - Siyal, A. A.; Samo, S. R.; Siyal, Z. A.; Mukwana, K. C.; Jiskani, S. A.; Mengal, A. (Engineering, Technology & Applied Science Research, 2019)
Increased traffic density due to urbanization is a major cause of air quality deterioration. Atmospheric particulate matter (PM) constitutes one of the most challenging issues in environmental research. This study was designed to assess PM10 and PM2.5 pollution at ten main locations in Nawabshah. Analysis of PM10 and PM2.5 pollution was carried randomly at different selected locations of the city. The highest concentration of PM10 was found at Mohini bazar (MB) and the highest concentration for PM2.5 was found at New Naka (NN). The mean concentration of PM10 was 78.3% higher than world health organization (WHO) standards and 35% than Pakistan’s National Environmental Quality Standards (NEQS). The mean concentration of PM2.5 was 47.3% and 26.3% higher respectively. Mean concentrations of PM2.5 on day-2 and day-10 were found lower than those set by NEQS, while mean concentrations of PM10 on all days exceeded the WHO and NEQS standards indicating that the city was heavily polluted more with PM10 than with PM2.5. Re-suspension of dust particles due to traffic flow, open burning of unmanaged solid waste on the sides of the road and in the street, and improper handling of construction and demolition waste were identified as the main sources for PM pollution in the city. Exposure to higher levels of PM10 and PM2.5 can cause health problems. High levels of PM10 and PM2.5 are a call for the implementation of strict measures to control PM pollution at Nawabshah in order to protect public health and the environment.